2020
DOI: 10.1038/s41598-020-68878-3
|View full text |Cite
|
Sign up to set email alerts
|

Human essential hypertension: no significant association of polygenic risk scores with antihypertensive drug responses

Abstract: Polygenic risk scores (PRSs) for essential hypertension, calculated from > 900 genomic loci, were recently found to explain a significant fraction of hypertension heritability and complications. To investigate whether variation of hypertension PRS also captures variation of antihypertensive drug responsiveness, we calculated two different PRSs for both systolic and diastolic blood pressure: one based on the top 793 independent hypertension-associated single nucleotide polymorphisms and another based on over 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
4
12
1
1
Order By: Relevance
“…As reproducibility of PGSs is extremely important, we also examined how many articles provided information outside of the Polygenic Score Catalog regarding the variants included in the PGSs (e.g., reference single‐nucleotide variant identification, effect sizes, etc.) and found that an additional nine articles provided this information in their supplementary data 39,57,58,59,60,67,68,69,72 . While these data were not provided for articles falling into categories relating to mental health and behavioral disorders, in the majority of cases PGSs were derived from data obtained from the Psychiatric Genomics Consortium (PGC), for which the summary‐level data are easily accessible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reproducibility of PGSs is extremely important, we also examined how many articles provided information outside of the Polygenic Score Catalog regarding the variants included in the PGSs (e.g., reference single‐nucleotide variant identification, effect sizes, etc.) and found that an additional nine articles provided this information in their supplementary data 39,57,58,59,60,67,68,69,72 . While these data were not provided for articles falling into categories relating to mental health and behavioral disorders, in the majority of cases PGSs were derived from data obtained from the Psychiatric Genomics Consortium (PGC), for which the summary‐level data are easily accessible.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles examined the association between a PGS derived from a coronary artery disease GWAS and response to low‐density lipoprotein lowering medications, with two reporting significant associations 38,56,57 . Of the two studies that examined antihypertensives responses, only one study reported a significant association; however, the base cohort that was used to inform the PGS was small ( n = 248) 58,59 . Finally, significant associations were reported for a PGS derived from a GWAS of QRS duration (electrical heart pattern) and Brugada syndrome/response to the antiarrhythmic agent ajmaline, 60 as well as for a diverticular disease PGS and nicorandil intolerance ( Table ) 61 …”
Section: Resultsmentioning
confidence: 99%
“…One such recent study evaluated the association of a genome‐wide PRS (>1 million SNPs) with antihypertensive drug responses. This was conducted across four BP drug classes based on data with a sample of n ∼200 per drug using BP data before and after 4 weeks on monotherapy; however, no association was established [68]. Utilizing risk scores in this way is an area of research in its infancy, and this is reflected in the small sample sizes studied and consequently lower power which could influence the results obtained so far.…”
Section: Risk Prediction and Causal Mechanismsmentioning
confidence: 99%
“…Загалом -це близько 1,1 мільярда постраждалих дорослих у всьому світі. За оцінками, щорічно гіпертензія призводить до приблизно 9,4 мільйона смертей [1]. На сьогодні, згідно сучасним уявленням, есенціальна гіпертензія (ЕГ), як провідний фактор ризику розвитку серцево-судинних захворювань є результат поєднання генетичних, екологічних та соціальних детермінант [2].…”
Section: вступunclassified